THEORETICAL ASPECTS OF MEASURING THE EFFICIENCY OF PUBLIC PROCUREMENT EXPENDITURE (World of finance, 2023)
Introduction. Funds of territorial communities are an important financial tool for the development of such entities of local self-government. Effective use of funds is the main problem in the development of the community, including in the implementation of public purchases, which are the target directions of the formation of social and economic benefits of the residents of the community. There is currently no model for evaluating the effectiveness of expenditures during public procurement and it is an object of study and formation at the theoretical and practical levels.The purpose of the article is to determine the theoretical and methodological aspects of public procurement and to develop criteria and levels of evaluation of the effectiveness of public procurement in Ukraine.Results. The principles of public procurement and the main approaches of scientists to identifying criteria for the effectiveness of public procurement have been studied. It was established that the efficiency criteria should be determined on the basis of: current legislation, i.e. normative-legal documents on public procurement and on the basis of generally accepted scientific norms. It is justified that the implementation of public procurement should be based on the principle of balancing economic, ecological and social criteria in order to achieve the most effective procurement in conditions of sustainable development.Conclusions. Proposals for identifying criteria for the most effective public procurement are substantiated, in particular: reducing the level of corruption, creating conditions for comfortable living of the population, increasing the economic use of natural resources, increasing the economic use of public funds, etc. The levels of evaluation of the effectiveness of public procurement and the peculiarities of their evaluation at each of the proposed stages are highlighted.